2014
DOI: 10.1155/2014/561351
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk for Vitamin D Deficiency in Obese Children with Both Celiac Disease and Type 1 Diabetes

Abstract: Background. It is unknown whether the coexistence of type 1 diabetes (T1D) and celiac disease (CD) increases the risk for vitamin D deficiency. Aims. To determine the vitamin D status and the risk for vitamin D deficiency in prepubertal children with both T1D and CD compared to controls, TID, and CD. Subjects and Methods. Characteristics of 62 prepubertal children of age 2–13 y with either CD + T1D (n = 22, 9.9 ± 3.1 y), CD only (n = 18, 8.9 ± 3.3 y), or T1D only (n = 22, 10.1 ± 2.8 y) were compared to 49 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Time course studies of diagnosis of type 1 diabetes and CD suggests that diagnosis of type 1 diabetes usually occurs first, followed by CD[ 63 - 66 ]. In patients with type 1 diabetes and celiac disease, additional autoimmune diseases may later develop, particularly autoimmune thyroid disease[ 67 - 69 ]. Moreover, risk of disease complications, including bone disease, retinopathy or nephropathy may occur, particularly if concomitant CD is present[ 67 - 71 ], and symptoms associated with CD may be more difficult to resolve if type 1 diabetes is also present[ 69 ].…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Time course studies of diagnosis of type 1 diabetes and CD suggests that diagnosis of type 1 diabetes usually occurs first, followed by CD[ 63 - 66 ]. In patients with type 1 diabetes and celiac disease, additional autoimmune diseases may later develop, particularly autoimmune thyroid disease[ 67 - 69 ]. Moreover, risk of disease complications, including bone disease, retinopathy or nephropathy may occur, particularly if concomitant CD is present[ 67 - 71 ], and symptoms associated with CD may be more difficult to resolve if type 1 diabetes is also present[ 69 ].…”
Section: Diabetesmentioning
confidence: 99%
“…In patients with type 1 diabetes and celiac disease, additional autoimmune diseases may later develop, particularly autoimmune thyroid disease[ 67 - 69 ]. Moreover, risk of disease complications, including bone disease, retinopathy or nephropathy may occur, particularly if concomitant CD is present[ 67 - 71 ], and symptoms associated with CD may be more difficult to resolve if type 1 diabetes is also present[ 69 ]. Finally, a gluten-free diet (if CD is present) may lead to better glycemic control and protect patients against development of diabetes-related vascular complications[ 70 ].…”
Section: Diabetesmentioning
confidence: 99%
“…Numerous epidemiological studies have suggested that vitamin D may have a role in defense against diabetes (5,6). Vitamin D deficiency is prevalent among the diabetic population; early and long-term vitamin D supplementation is associated with a decrease in the risk of developing diabetes, and the incidence of T1DM is greater in areas with fewer days of sunlight per year (7,8). However, the underlying mechanisms of the involvement of vitamin D in T1DM remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed lower vitamin D levels in overweight patients and ones with T1D [ 69 , 70 ]. Vitamin D supplementation was associated with improved blood vessel function in children with diabetes [ 70 , 71 ]. Whether vitamin D supplementation can be preventive in the general population or those likely to develop CVD is still open to debate [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%